Sulfur Transfer Melt Infiltration for High‐Power Carbon Nanotube Sheets in Lithium‐Sulfur Pouch Cells. Issue 6 (18th March 2021) - Boenke, Tom; Härtel, Paul; Dörfler, Susanne; Abendroth, Thomas; Schwotzer, Friedrich; Althues, Holger; Kaskel, Stefan
Abstract: Among next‐generation battery systems, the lithium‐sulfur (Li−S) technology is attracting increasing attention driven by the low active material costs, high theoretical specific energy, and promising progress made in terms of its technology readiness level (TRL) in the recent years. However, the power density, especially in prototype cells, is an often neglected parameter being crucial for future application sectors. In this work, the cathode is redesigned by introducing a scalable, non‐toxic, and homogeneous sulfur impregnation process for free‐standing carbon scaffolds and tailorable sulfur areal loading. This novel sulfur transfer melt infiltration is exemplarily applied to process carbon nanotube (CNT)‐based Li−S cathode structures, but as a generic and scalable methodology is highly versatile. We demonstrate the development for CNT Buckypaper (BP) and CNT powder‐based dry transfer electrodes (DryFilm) as cathode host structures with the highly polysulfide (PS) solvating electrolyte system DME/DOL. In order to evaluate the practicability for high power application, the redesigned CNT BP cathode system with varying sulfur contents is employed in multi‐layered pouch cell format with 4 μL mgS −1 for reduced electrolyte conditions. Additionally, first pouch cells with circular perforated aluminum current collector enable 80 % weight savings of passive cathode material without compromising cell performance for free‐standing thin‐film cathodes. This study is an important step towards the development of lightweight Li−S cells for high power applications, such as drones or high altitude satellites. Abstract : Lightweight cells : Novel sulfur transfer melt infiltration for free‐standing CNT Buckypaper and CNT dry transfer electrodes (DryFilm) enable the redesign of lithium‐sulfur cathode structure. The electrochemical performance is evaluated in terms of rate capability and varying sulfur loadings in state‐of‐the‐art electrolyte DME/DOL in multi‐layered pouch cells. Full area and circular perforated aluminum current collector concepts were studied regarding high power application with thin‐film cathodes with low sulfur loadings.